Sistem Penunjang Keputusan dalam Penentuan Prioritas Pembanguanan Menggunakan Metode Trus Base dengan Topsis - Beni Aktavera; Sumijan (SAFE-Network, 2020)
Village communities need empowerment in order to develop community welfare and independence to increase attitudes, knowledge, behavior, skills, and priority needs of the village community, including development. villages must be done well in an effort to community village. Village development has an context. Research is to assist Merangin district in making decisions to determine priorities for sub-district development, Merangin Regency which refers to the Regional Long-Term Development Plan (RPJPD). 2018-2019 and 2020 budgets while the decision-making method to solve existing problems is to use increased public participation using a trust-based (trust-based). With the TOPSIS (Technique For Others Preference by Similarity to Ideal Solution) method. With the method to be used, this system can provide information in the form of proposals which are prioritized to be implemented which are aligned with the Regional Long-term Development Plan (RPJPD) and the National Medium Term Development Plan (RPJMN) so that village development can be carried out properly, the TOPSIS method used was able to overcome the weaknesses in the old system and gave 90% accurate results in determining the development priorities of Merangin Regency using the method TOPSIS, and the application of the topsis method for this system could contribute to the results of ranking alternative development priorities in Kab. Merangin to the maximum.